Stigma and Prosthetic Rehabillitation Chalange for Leprosy Survivor in Pandemic Situation - Melinda Harini; Steven Setiono; Luh Karunia Wahyuni; Sri Linuwih Menaldi; Satyanaya Widyaningrum; Edbert Wreksoatmojo (Indonesian Journal of Physical Medicine & Rehabilitation, 2022)
Indonesia ranks third in terms of countries with the highest number of leprosy in the world. This fact hasn't changed since 20 years ago. This shows the magnitude of leprosy management problems, both at the world level and national level. These problems range from the problem of finding new cases, continuity of the provision of various drug regimens, and control of the spread. In addition to problems related to the detection and handling of new cases, there are also problems in leprosy survivors. Survivors generally have disabilities due to the disease. The disability can continue to be aggravated over time, even though leprosy itself has healed long since. These disabilities vary from numbness, paralysis, shortened and claw-like fingers on the hands and feet, wounds resulting in amputations of the nose, ears, fingers and limbs. Such problems require a complete and continues management. Meanwhile, the management of leprosy, both in patients and survivors, has challenges both in terms of medical, policy, financing, and culture. Not to mention the challenges related to low socialistism, not many Indonesians know the problem of leprosy, especially knowing the magnitude of the problem. Pandemic conditions make things worse. This case report will explain the journey of leprosy survivor who has been amputated and has rehabilitation related to the maintenance and replacement of leg prosthetic in pandemic situation. It will describe the stigma, medical, and socioeconomic challenges that he has to go through. This case report is expected to be an inspiration in improving public, academics, policy makers, and stakeholder awareness, related to leprosy handling problems in Indonesia, both problems for patient and survivors. Thus, it is ultimately expected to reduce the level of disability, promote equal rights for people with disabilities, and support the realization of leprosy elimination nationally and internationally.